KEPERCAYAAN MASYARAKAT TERHADAP RITUAL MEMINDAHKAN HUJAN DI KECAMATAN TUALANG KABUPATEN SIAK - Sintia Kurnia; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research analyzes community's trust toward rain-moving ritual in Tualang Subdistrictof Siak Regency. This research is a social study that happened in Tualang sub-district,in which the position of rain-handler in society is very important. Rain-handler is a figurewho has advantages in the field of moving rain that is trusted by Tualang District communityuntil now. Rain-handler is often requested by the community in various celebrations;especially held in open area. The community's trust is strongly supported by the role of therain-handler in the social activities of Tualang Sub-district. The theory that uses in thisresearch is theory according to Auguste Comte. Data analysis was computed by usingqualitative descriptive, data retrieval technique in this research is purposive where thenumber of respondents is 6 people consisting of Tualang District. Based on the researchresults in the field, it shows that public confidence toward the rainy handler until this day isstill exist used by the Tualang District community who is a native inhabitants of that area.Keywords: Trust, Ritual, Rain-handler